2015
DOI: 10.3390/nu7125499
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Vitamin 25(OH)D Status as a Risk Factor for Receptive Language Development: A 24-Month, Longitudinal, Observational Study

Abstract: Emerging data suggest that vitamin D status during childhood and adolescence can affect neurocognitive development. The purpose of this study was to investigate whether gestational 25(OH)D status is associated with early childhood cognitive and receptive language development. The Conditions Affecting Neurocognitive Development and Learning in Early Childhood Study (CANDLE) study enrolled 1503 mother-child dyads during the second trimester of healthy singleton pregnancies from Shelby County TN. Among 1020 parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 52 publications
0
45
1
Order By: Relevance
“…Participants were enrolled in the Conditions Affecting Neurocognitive Development in Early Childhood (CANDLE) study, a prospective prenatal cohort in Memphis, Tennessee. Briefly, 1503 healthy women, 16‐40 years of age, with a singleton pregnancy, and intent to deliver at a study hospital were enrolled during 16‐28 weeks estimated gestational age (EGA) from community‐based obstetric practices between 2006 and 2011 . The CANDLE study included 2nd and 3rd trimester and delivery visits during which we obtained demographics, psychosocial and medical histories, and biospecimens.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were enrolled in the Conditions Affecting Neurocognitive Development in Early Childhood (CANDLE) study, a prospective prenatal cohort in Memphis, Tennessee. Briefly, 1503 healthy women, 16‐40 years of age, with a singleton pregnancy, and intent to deliver at a study hospital were enrolled during 16‐28 weeks estimated gestational age (EGA) from community‐based obstetric practices between 2006 and 2011 . The CANDLE study included 2nd and 3rd trimester and delivery visits during which we obtained demographics, psychosocial and medical histories, and biospecimens.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, 1503 healthy women, 16-40 years of age, with a singleton pregnancy, and intent to deliver at a study hospital were enrolled during 16-28 weeks estimated gestational age (EGA) from community-based obstetric practices between 2006 and 2011. 18,19 The CANDLE study included 2nd and 3rd trimester and delivery visits during which we obtained demographics, psychosocial and medical histories, and biospecimens. Mother-child dyads were followed with in-person study visits annually.…”
Section: Study Populationmentioning
confidence: 99%
“…Seven studies did not find any association between prenatal vitamin D levels and global IQ or cognitive development at preschool [69][70][71][72] and school age [73,74]. However, Keim et al [75] reported a positive association between both maternal and cord blood 25(OH)D concentration and IQ at age 7, but the effect estimates were very small.…”
Section: Global Intelligence Quotient (Iq) or Cognitive Developmentmentioning
confidence: 99%
“…A growing body of evidence suggests that low maternal 25(OH)D levels during pregnancy are associated with impaired neurodevelopmental and neurocognitive outcomes during infancy and childhood [117,[224][225][226][227][228]; however, not all studies are in agreement [229,230]. In this regard, several studies have shown a significant association between suboptimal maternal vitamin D status and reduced language developmental outcomes in the offspring [224][225][226].…”
Section: Offspring Brain Development and Functionmentioning
confidence: 99%